ANALYSIS OF THE NEEDS FOR DEVELOPING LEARNING VIDEOS ON THE MATERIAL OF EARTH'S ROTATION EVENTS IN GRADE VI OF SDN RANTAU PANGERAN - Zurmanely; Ketang Wiyono; Ermayanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the need for learning videos on the rotation event material to train the problem-solving skills of grade VI elementary school students. The background of this study is based on the many students who have difficulty in understanding the material on the rotation of the earth and the results of observation data conducted by researchers indicate that the learning process is still centered on textbooks and oral explanations from teachers without the help of contextual and interesting learning media. This study uses a qualitative method with a descriptive approach and a needs analysis questionnaire. The subjects of the study consisted of teachers and grade VI students at SDN Rantau Pangeran. Data collection was carried out through observation, interviews, and distribution of needs analysis questionnaires. The results of the analysis show that students need learning media that are interesting, easy to access, and can improve students' ability to solve problems. The selection of video-based learning media is considered to be able to increase students' motivation and ability to solve problems, especially on the material on the rotation of the earth. The results of the study showed that generally students (80.75%) still do not understand the material related to the rotation of the earth and show low problem-solving skills. 73.50% of students are interested in video-based learning media because they are more interesting, concise, easy to access, and easy to understand. Based on these findings, it can be concluded that the development of learning videos on the material of the earth's rotation to improve students' problem-solving skills is seen as the right solution. The research data is expected to be useful as basic data in the development of learning videos on the material of rotation events in grade VI of elementary school.